PENGARUH MODEL PEMBELAJARAN STS (SCIENCE, TECHNOLOGY, AND SOCIETY) TERHADAP KETERAMPILAN MEMBUAT KEPUTUSAN SISWA - Defiana Aliyatur Rosidah; Hairida Hairida; Masriani Masriani (EduChem, 2022)
The aim of this study were to determine the differences of the  student's decision making skills before and after being taught using the STS (Science, Technology, and Society) learning model at MAN 3 Pontianak. The form of this research is pre-experimental design with the research plan of one group pretest-posttest design. The sample of this research is class X MIPA as an experimental class. The data collection tools used are the decision making skills test instrument and interview guidelines. Decision making skills were analyzed using the Wilcoxon test. The analysis is smaller than the significant level of 0.05 which means there are differences in decision making skills in class X MIPA MAN 3 Pontianak on scientific method sub-material before and after learning using STS ( Science, Technology, and Society) learning model. The n-gain calculation results obtained a value of 0.32, so the conclusions obtained that the STS (Science, Technology, and Society) learning model  affect student’s decision making skills in the medium category. Keyword : STS (Science, Technology, and Society) , Keterampilan Membuat Keputusan, Metode Ilmiah